Efficacy of Selected Antibiotics Against Porphyromonas Gingivalis Isolated from Periodontal Infections: In Vitro Study (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background:Porphyromonas gingivalis is a key pathogen associated with periodontitis, a chronic inflammatory disease of the supporting structures of the teeth. Due to the rising resistance to conventional antimicrobial agents, P. gingivalis is resistant to many antibiotic treatments. The study aimed to describe in vitro susceptibility of P. gingivalis to 10 registered antibiotics.Materials and Methods: Bacterial samples were collected from patients diagnosed with periodontitis. The study was conducted in vitro using Antimicrobial Susceptibility Testing (AST) including (Amoxicillin, Clindamycin, Penicillin, Ciprofloxacin, Nalidixic Acid, Amikacin, Imipenem, Gentamicin, Oxacillin, and Tetracycline) and was assessed using the disc diffusion method.Results:The sensitivity of 15 Porphyromonas gingivalis isolates to ten antibiotics was evaluated using the disk diffusion method. The results showed a clear variation in the response of the isolates to the antibiotics, with Imipenem and Tetracycline recording the highest mean inhibition zones respectively, indicating their high effectiveness against the studied isolates.In contrast, some antibiotics showed weak or no efficacy, such as penicillin and oxacillin, with most isolates showing complete resistance to them. These results reflect the widespread prevalence of acquired resistance mechanisms in P. gingivalis, particularly against traditional antibiotics such as penicillin.Conclusion:The widespread use of antibiotics has led to significant resistance in key periodontal pathogens, underscoring the importance of susceptibility testing and careful consideration of resistance profiles in clinical practice to optimize treatment strategies.